CHARACTERIZATION OF PULAUBALANG FORMATION AND TANJUNG FORMATION COALS TO SUPPORT GASIFICATION UTILIZATION WITH TGA-MS METHOD APPROACH - Al Hamda, Aisyah
Coal has become a major commodity to supply and fulfill energy needs around the world. The use of coal is very diverse, but its use is carried out by direct combustion which provides environmental problems in the form of harmful carbon emissions. Thus, it is necessary to have a more environmentally friendly technology, one of which is gasification. This study was conducted to determine the effect of coal characteristics on thermal behavior and gas products produced by coal during heating. The chemical analysis carried out consists of proximate analysis, ultimat, calorific value, and ash composition. Thermogravimetric-mass spectrometry (TG-MS) analysis was conducted to determine the thermal characteristics during the gasification process. The coal samples used came from the Pulaubalang Formation (BB-01) and the Tanjung Formation (BB-02). The results of gasification experiments in both environments show that sample BB-01 is more reactive in a CO2 environment with the products produced consisting of H2, H2O, and CO, while sample BB-02 is more reactive in a limited O2 environment with the products produced consisting of CO2 and H2O. Thus, sample BB-01 is more suitable for CO2 gasification because it tends to produce syngas, compared to sample BB-02 in limited O2 which tends to produce combustion products.